STRATEGIES FOR LANGUAGE TEACHING AND THEIR INFLUENCE ON EARLY CHILDHOOD COGNITIVE DEVELOPMENT - Smith Morán, Karina; Hinostroza Carriel, Edgar Roberto; Hinostroza Carriel , Erika Iliana; Hurtado Escudero, Blanca Elizabeth (Revista Minerva, 2024)
This study investigates how language influences cognitive development during early childhood, focusing on children from the "Dolores Cacuango" Educational Unit in Guayaquil, Ecuador. Through direct observations and visits to the institution, significant problems related to language quality were identified, which have a direct impact on students’ learning and cognitive development. These difficulties in verbal expression not only limit children’s ability to communicate effectively, but also affect their ability to solve problems and actively participate in educational activities. The main purpose of the research was to analyze the pedagogical strategies that teachers implement in the classroom and how they influence the academic performance of students. To this end, a qualitative approach was used, which included the application of surveys and interviews with teachers and legal representatives, with the aim of obtaining a comprehensive view of the problem and perceptions of language development in children. The results indicate that strengthening language development has the potential to contribute significantly to the comprehensive development of students’ cognitive abilities, improving both their communication skills and their overall academic performance during early childhood.